Le storie e la memoria - Delle Donne, Roberto; Zorzi, Andrea (Firenze University Press, 2002)
This book is a collection of contributions by the Italian scholarship fellows at the Deutsches Historisches Institut of Rome over the last decade. It is intended as a tribute to one of the leading mediaevalists at international level, a scrupulous and sensitive scholar of Italian history. Over and above all this, it is a sign of gratitude from the young academics who have been able to consolidate their research thanks to such scholarships. Consequently the 14 contributions that make up the book do not share the academic orientation of any particular school, but range over various research sectors and different chronological periods.
Il volume, che raccoglie i contributi di ex borsisti italiani dell'ultimo decennio del Deutsches Historisches Institut di Roma, vuole essere un omaggio a uno dei medievisti più noti a livello internazionale e all'attento e sensibile studioso della storia italiana, ma soprattutto un segno di gratitudine di giovani studiosi che con tale borsa hanno potuto consolidare i loro percorsi di ricerca. I 14 contributi che lo compongono non sono quindi accomunati da un comune orientamento formativo di scuola, ma spaziano fra diversi settori di ricerca e differenti ambiti cronologici.
Italian
Keywords: Medieval history; deutsches historisches institut; arnold esch